2015
DOI: 10.2174/1874325001509010163
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Survival of Acetabular Reinforcement Rings/Cages for Complex Hip Arthroplasty

Abstract: Introduction : Acetabular reinforcement rings/ cages (AR) are commonly used for reconstruction of bone defects in complex hip arthroplasty. The aim of this study was to retrospectively investigate the 10-year survival rate of Ganz reinforcement rings and Burch-Schneider cages used in a single institution.Material and Methods : Between September 1999 and June 2002 all ARs, implanted in one institution, were identified. All patients had regular clinical and radiographic follow-up and were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…They concluded that appropriate application of titanium cage can be effective to maintain stability and restore bone stock in the long term. [11][12][13] In this series we report up to 17 years of follow-up (average 7 years) of titanium reconstruction cages on 56 hips in 54 patients. To the best of our knowledge, this is the longest follow-up series of titanium cages in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They concluded that appropriate application of titanium cage can be effective to maintain stability and restore bone stock in the long term. [11][12][13] In this series we report up to 17 years of follow-up (average 7 years) of titanium reconstruction cages on 56 hips in 54 patients. To the best of our knowledge, this is the longest follow-up series of titanium cages in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Ewers et al 13 reported 77.7% survival at 10 years with trabecular titanium in acetabular revisions. Steno et al 14 review 81 hips revised with trabecular metal and reported 1 revision case at 38 months.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to use a trabecular metal augment. Due to damage to the medial wall and column in type 3 (Table 1, Figure 1, Figures 7-9), it is imperative to use a cup-cage system to prevent protrusion [31]. Like a reinforcement cage.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-protrusio cage is useful for treatment of severe acetabular rim and cranio-lateral border of the acetabulum bone defects and also in older patients owing to less acetabular support following osteoporosis. Moreover, with use of anti-protrusio cage, larger areas of acetabular loss could be bridged (17). There are several reports indicating the short-and long-term results of using the antiprotrusio cages in RTHA (15,(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%